Lowinson and Ruiz's substance abuse : a comprehensive textbook. - Ruiz, Pedro, 1936-; Strain, Eric C.; Lowinson, Joyce H. (Wolters Kluwer Health/Lippincott Williams & Wilkins, 2011)
"A comprehensive, authoritative text on all aspects of substance abuse and addiction medicine. Scientific topics such as the biology of various addictions and all dimensions of clinical treatment and management are addressed by a wide range of leading contributors. Behavioral addictions are addressed also, so the text is not solely devoted to specific substances and their misuse"--Provided by publisher.